The Role and Authority of Notaries in Ensuring the Legality of the Establishment of Village-Owned Enterprises (BUMDes) in Accordance with Government Regulation No. 11 of 2021 - Wiyati, Khadijah Ongtien Wahyuning; Sudirman, Hanifa; Pamungkas, Bayu Tri; Sanjaya, Alya Afiffa Raihana Nissa; Gultom, Elisatris (Al-Qanun: Jurnal Kajian Sosial dan Hukum Islam, 2025)
This study examines the role and authority of notaries in ensuring the legality of establishing Village-Owned Enterprises (BUMDes) in accordance with the provisions of Government Regulation No. 11 of 2021. BUMDes, as an economic entity established by villages, plays a crucial role in improving the welfare of the village community. However, many BUMDes lack legal entity status, leading to unclear legal accountability and potential legal issues in managing village assets. This research employs a normative juridical method with a legislative approach to analyze the role of notaries in creating establishment deeds and the legal entity confirmation of BUMDes. The study findings indicate that notaries play a critical role in guaranteeing legal certainty and accountability in BUMDes management, as well as protecting the village assets being managed. The research also identifies challenges in the implementation of this regulation and provides recommendations to strengthen collaboration between notaries and village governments.